Kerguelen hotspot magma output since 130 Ma - Mike Coffin; MS Pringle; RA Duncan; TP Gladczenko; M Storey; RD Muller; LA Gahagan (2002)
The Kerguelen hotspot (Indian Ocean) has produced basalt for ¡130 Myr, among the longest known volcanic records from a single source. New and published 40Ar/39Ar age determinations from the Kerguelen Plateau, Broken Ridge, Rajmahal Traps, and Bunbury basalts, and of Indian and Antarctic dikes help to document the hotspot¡¯s history. Using radiometric dates and crustal structure determined from geophysical data and drilling results, we calculate the magmatic output of the Kerguelen hotspot through time. Output rates have varied in ways not predicted by current geodynamic models; maximum eruption volumes postdate the initial surface manifestation of the hotspot as well as break-up between Antarctica and India by ¡Ã15 Myr, and magma output rates were high, as well as geographically diverse, over an interval of 25 Myr, from ¡120 to ¡95 Ma. We propose two alternatives to the standard mantle plume paradigm, one involving multiple plume sources, and another consisting of a single, but dismembered plume source.